SISTEM PENDUKUNG KEPUTUSAN PEMBELIAN ALAT OUTDOOR METODE TOPSIS: Sistem Pendukung Keputusan Pembelian Alat Outdoor Metode Topsis - Gangsar Yusuf Prastoto (JURNAL ILMIAH INFORMATIKA, 2019)
Decision support system is a system that is able to solve problems efficiently, effectively, which aims to assist decision making by choosing various alternative decisions. With the application of system software to support the decision to purchase outdoor tools using the topsis method to facilitate natural activists for decision making. In this study the method used is the topsis method and used to select the Outdoor tool based on the concept that the best alternative not only has the shortest distance from a positive ideal solution but also has the farthest distance from the negative ideal solution. This decision support system is made to make it easier for natural activists to easily make choices in order to get the desired item.